Control method of the quantitative content of liquefied petroleum gas comprnents and device for its realization - Книш, Богдан Петрович (Technology audit and production reserves, 2014)
The quantitative value of liquefied petroleum gas, such as methods of its measurement and sensors based on them, are shown in the article. It is proved that determine the mass fraction of liquefied petroleum gas is critical because the constant improvement of liquefied petroleum gas quality control is very important for industry today. The aim of work is developing a method for controlling the quantitative content of liquefied petroleum gas components and experimental unit for its implementation. To achieve this aim it is necessary to develop a method for determining the quantitative content of components in the mixture of liquefied petroleum gas, that improving a general accuracy due to taking into account not only the quantitative composition of propane and butane, but impurities, that affect the quality of liquefied petroleum gas and have a detrimental effect on manufacturing equipment and unit due to the temperature parameters, confirming the adequacy of the proposed method.